Superparasitism, immune response and optimum progeny yield in the gregarious parasitoid Palmistichus elaeisis. Issue 6 (27th February 2017) - de S Pereira, Kleber; Guedes, Nelsa Maria P; Serrão, José E; Zanuncio, José C; Guedes, Raul Narciso C
Abstract: BACKGROUND: The subsequent deposition of an egg clutch by a female parasitoid into a host already parasitised either by itself or a conspecific (i.e. superparasitism) is a counterintuitive adaptive strategy, particularly considering the female parasitoid's ability to recognise the parasitised hosts. Such a scenario suggests that the adaptive value of superparasitism depends on the number of clutches laid in the same host, with consequences for parasitoid progeny yield. Here, we tested whether such is the case for the gregarious parasitoid Palmistichus elaeisis and explored its underlying basis. RESULTS: Allowing female parasitoids to lay multiple egg clutches in a single melonworm host pupa, parasitoid progeny and fitness exhibited a peak or optimum at three egg clutches laid per host pupa. In addition, haemocyte count, encapsulation and melanisation decreased with the number of egg clutches laid per host pupa. DISCUSSION: An optimum number of three clutches laid per host pupa was detected for P. elaeisis . As immune response via haemocyte production, encapsulation and melanisation decreased with the number of clutches laid per host, the higher parasitoid yield and fitness observed is the likely consequence of a compromised immune response coupled with an accommodative (i.e. scramble) larval competitive strategy allowing enough resources for optimum balance of parasitoid number and quality produced. © 2017 Society of Chemical Industry